Pengaruh Latihan Burpee dan Box Jump Terhadap Daya Ledak Otot Tungkai dan Kecepatan Renang 50 Meter Gaya Bebas - Wicaksono, Teguh; Putri, Wahyu Setia Kucahyaning (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2020)
The research is almed ti analyze (1) The influence of burpee workout on leg muscle explosive power and swmming speed (2) The influence of box jump workout on workout on leg muscle explosive power and swimming speed (3) The difference of burpee and box jump workout on leg muscle explosive power and swimming speed. This research is quasi experimental research with quantitative descriptive analysis. It is a population research where the number of population and samples are same. They are 24 athletes which contain of 8 athletes in experimental group I, 8 athletes in experimental group II and 8 athletes in control group. The data research is ordinal pairing. In collecting data of leg muscle explosive power, the researcher uses stopwatch, jump md and scale while in collecting data of swimming speed. The researcher uses stopwatch. The data analysis uses normality test, homogeneity test and T-test with SPSS 20.0. The finding of this research reveals that : (1) burpee workout can increase the leg muscle explosive power up to 6,98 % and swimming speed up to 4,55 % (2) box jumping workout can increase the leg muscle explosive power up to 8,13 % and swimming speed up to 3,53 % (3) box jump workout is the most effective workout to increase leg muscle explosive power and swimming speed in swimming club’s athletes of Taman Tirta Bojonegoro.